Development of Dynamic Brake Unit for Georgia EMUs - LIU Ye-ping; CHEN Yi-zheng; ZHANG Qiu-hong; HE Zhai (机车电传动)
Principle, technology characteristic, performance parameter, and composition of dynamic brake unit (DBU) in EMUsexported to Georgia were introduced. Resistor units of the DBU adopted drawer type design for easy installation and maintenance, and hadthe features of non-deformability and big hottest-spot temperature allowance. Tests and practical running proved that DBU was stably andcredibly.